2011
DOI: 10.1128/jvi.05841-11
|View full text |Cite
|
Sign up to set email alerts
|

CD8+T Cell Escape Mutations in Simian Immunodeficiency Virus SIVmac239 Cause Fitness DefectsIn Vivo, and Many Revert after Transmission

Abstract: Virus-specific CD8؉ T lymphocytes select for escape mutations in human immunodeficiency virus (HIV) and simian immunodeficiency virus (SIV). To assess the effects of these mutations on viral fitness, we introduced escape mutations into 30 epitopes (bound by five major histocompatibility complex class I [MHC-I] molecules) in three different viruses. Two of these MHC-I alleles are associated with elite control. Two of the three viruses demonstrated reduced fitness in vivo, and 27% of the introduced mutations rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…This observation provides strong evidence for convergent evolution in these species, both evolving a similar binding motif . It has been proposed that the preference of Mamu-B*08, and HLA-B*27, for peptides carrying Arg both at P1 and P2, may mean that the epitopes restricted by these alleles are located in protein regions of particular structural significance, that is, containing adjacent Arg residues, and as a result that are highly resistant to escape (Mudd et al, 2011). There is also similarity in the peptide-binding groove of the protective macaque allele Mamu-B*17 and HLA-B*57/58:01, HLA-A*25 and HLA-A*32, all of which have a strong preference for Trp at PC.…”
Section: Introductionmentioning
confidence: 99%
“…This observation provides strong evidence for convergent evolution in these species, both evolving a similar binding motif . It has been proposed that the preference of Mamu-B*08, and HLA-B*27, for peptides carrying Arg both at P1 and P2, may mean that the epitopes restricted by these alleles are located in protein regions of particular structural significance, that is, containing adjacent Arg residues, and as a result that are highly resistant to escape (Mudd et al, 2011). There is also similarity in the peptide-binding groove of the protective macaque allele Mamu-B*17 and HLA-B*57/58:01, HLA-A*25 and HLA-A*32, all of which have a strong preference for Trp at PC.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, this "escaped" virus did not replicate as well as WT SIVmac239 in vivo, but it is not clear if this impaired replicative capacity was due to A 136 P or the other changes introduced in its backbone. Notably, a characterization of the viral quasispecies circulating in those animals in the chronic phase revealed that the A 136 P substitution did not revert to WT, indicating that it can be stably maintained in vivo in the absence of CD8 ϩ T-cell-mediated pressure (41). Based on these data, one might envision a scenario in which SIV initially tries to evade the host CD8 ϩ T-cell response by mutating the internal residues of Nef RL10, even though sequence variation within this highly conserved epitope is probably disadvantageous for the virus.…”
Section: Figmentioning
confidence: 99%
“…In contrast, preferential targeting of the HIV envelope (Env) protein has been associated with higher viral loads in both human and monkey studies (17)(18)(19)(20). Although the precise mechanisms responsible for the enhanced antiviral function associated with Gag-specific responses are not fully understood, fitness costs associated with escape mutations from CD8 ϩ T cell responses directed at the highly conserved Gag protein have been implicated in both humans infected with HIV and primates infected with simian immunodeficiency virus (SIV) (21)(22)(23)(24)(25)(26)(27).…”
Section: Ost Human Immunodeficiency Virus (Hiv)-infected Individualmentioning
confidence: 99%